The Cultural Dimensions of Hofstede in the Chinese Company Zhe Jiang Deman - ortiz, ricardo; Valencia, Fernando; Scott, Pilar (Archives of Business Research, 2022)
The corporate culture in a company is essential to achieve organizational objectives. The objective of this research is to describe the cultural profiles of those who work as employees in a Chinese manufacturing company, taking Hofstede's cultural dimensions as a reference framework. Geert Hofstede describes organizational culture in a general way, using the following cultural dimensions: power distance, individualism-collectivism, masculinity-femininity, uncertainty avoidance, short- and long-term orientation, and indulgence-restraint. This article is a case study that uses frequency graphs and Cronbach's Alpha validation test, which allows us to contribute to a simple but scientifically orthodox and correct methodology to describe the organizational culture in any institution or company of any nationality. The results will allow companies or organizations to make strategic decisions. Keywords: organizational culture, Hofstede model, case study.